A review: lead free solder and its wettability properties. Issue 3 (6th June 2016) - Mhd Noor, Ervina Efzan; Mhd Nasir, Nur Faziera; Idris, Siti Rabiatul Aisya
Abstract : Purpose: The purpose of this paper is to publish on the review of the lead free solder for electronic packaging. This involved the basic principles of the solder, the lead solder and its legislation and the lead free solder with its mechanism. In addition, this paper also reviews on the lead free solder characteristics that focused on its wettability. Design/methodology/approach: This paper approach on the review of the solder wettability on the surface. It reviews on the solder especially on the contact angle and surface tension that is covered under the wettability of the solder. Findings: This paper also reviews on the lead free solder characteristics that focused on its wettability. Originality/value: This paper summarized finding from other researchers. The authors collect and summarize the useful data from other papers or journals. It is to create an understanding for the reader by discussion from the others research papers findings.